Motivasi dan Kompensasi Berdampak Pada Peningkatan Kinerja Pegawai Non PNS (Studi Kasus di Salah Satu Sekolah Negeri Kota Bandung) - Rima Desyana Mawaddah; Nenny Hendajany (Jurnal Ekonomi Manajemen Perbankan, 2021)
This study aims to determine whether motivation and compensation can affect the performance of non-PNS employees. Respondents drawn from this study are all non-civil servant employees, so we use a census, with a total of 40 respondents. The method used in this research is descriptive analysis which aims to describe the performance of non-PNS servants. Data collection using questionnaires. The data from the questionnaire is in ordinal form and it is necessary to transform it into an interval scale. Data transformation can be performed using the Method of Successive Interval (MSI). To answer the research objectives, multiple regression analysis was used by first testing the classical assumptions. Based on the results of data analysis, it can be concluded that there is a significant influence between motivation and compensation on the performance of non-PNS employees. Worker motivation and compensation provided by an organization will improve the performance of non-PNS employees. Keyword: Motivation, Compensation, Employee Performance